Tuning the Photophysical and Electrochemical Properties of Aza‐Boron‐Dipyridylmethenes for Fluorescent Blue OLEDs. (21st April 2021) - Tadle, Abegail C.; El Roz, Karim A.; Soh, Chan Ho; Sylvinson Muthiah Ravinson, Daniel; Djurovich, Peter I.; Forrest, Stephen R.; Thompson, Mark E.
Abstract: A series of substituted aza‐boron‐dipyridylmethene (aD ) compounds are demonstrated as fluorescent dopant emitters in blue organic light emitting diodes (OLEDs). Replacing the meso ‐carbon of a dipyridylmethene dye with nitrogen to form the aD chromophore leads to a destabilization of the highest occupied molecular orbital in aD, as evidenced both from their experimentally determined photophysical and electrochemical properties. These properties are consistent with theoretical calculations of the molecular energetics. These aD derivatives emit violet to blue light, peaking between 400 and 460 nm with photoluminescent quantum yields over 85%. The aD compounds have small energy differences (<400 meV) between their singlet and triplet excited states. OLEDs fabricated with an aza‐boron‐dipyridylmethene emitting fluorophore give an external quantum efficiency of 4.5% on glass substrates, close to the theoretical maximum for fluorescent OLEDs. Abstract : A class of blue fluorescent boron‐aza‐dipyridylmethene with small excited state energy gaps (Δ E ST  < 400 meV) and high photoluminescence efficiencies ( Φ PL  > 0.8) leads to blue monochromatic devices with external quantum efficiencies close to the theoretical maximum. The synthetic and optical tunability along with the thermal and chemical stability of these materials make them viable options for organic optoelectronics.